Therapeutic challenges in managing Stenotrophomonas maltophilia bloodstream infection in a renal dysfunction patient: a case study and literature review - Fan, Xiongxiong; Chen, Feng; Ruan, Zhengshang; Li, Lixia (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe overall infection rate of Stenotrophomonas maltophilia has markedly increased over the past two decades, with its bloodstream infections being associated with poor clinical outcomes and high mortality rates. In patients with concomitant renal insufficiency, the complexity of anti-infective therapy is further heightened due to limited antibiotic options and altered pharmacokinetics, highlighting the critical importance of individualized treatment strategies.ObjectiveThis study aims to explore effective clinical treatment strategies for S. maltophilia-induced bloodstream infections in patients with renal insufficiency and to provide evidence-based support for optimizing antimicrobial decision-making.MethodsWe present a case of S. maltophilia bloodstream infection occurring in a patient with concomitant renal insufficiency. The choice of antimicrobial agents, dosage modifications, and combination therapy were systematically analyzed based on results from antimicrobial combination testing and observed clinical response. A comprehensive review of relevant literature was also conducted.ResultsGuided by the findings of antimicrobial combination testing, an individualized regimen consisting of ceftazidime-avibactam (CZA) and aztreonam (ATM) was implemented, with dose adjustments tailored according to the patient’s renal function. This approach led to the successful resolution of the infection. The literature review further supports that in patients with renal insufficiency, antimicrobial selection should be guided by considerations including nephrotoxic potential, spectrum of activity, and pharmacokinetic profiles. Combined susceptibility testing emerges as a valuable tool in tailoring effective therapeutic regimens.ConclusionThe combination of CZA and ATM, guided by antimicrobial susceptibility testing and adjusted according to individual patient characteristics, demonstrated both safety and efficacy in the treatment of S. maltophilia bloodstream infection.